Analisis Isi Muatan Higher Order Thinking Skills (HOTS) Dalam Evaluasi Buku Ayo Fasih Berbahasa Arab Untuk Kelas XI - Muqimah Liwais Sunnah; Thoriq Agus Shodiqin; Dewi Afiatul Qutsiyah; Ninik Indrawati (IAIN Bone, 2026)
This study aims to analyze the content of Higher Order Thinking Skills (HOTS) in the evaluation components of the textbook Ayo Fasih Berbahasa Arab for Grade XI Madrasah Aliyah. The study focuses on the presentation of HOTS and the tendency of cognitive levels reflected in the exercises and end-of-semester evaluation questions. This research employed a qualitative descriptive approach using content analysis. The data consisted of 35 questions taken from learning exercises and end-of-semester evaluations in the textbook. The questions were analyzed and classified based on the Revised Bloom’s Taxonomy into Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS). The findings reveal that 11 questions (31.43%) were categorized as LOTS, 12 questions (34.29%) as MOTS, and 12 questions (34.29%) as HOTS. HOTS-oriented questions were identified in tasks requiring students to analyze, interpret, infer, and synthesize information, whereas LOTS-oriented questions mainly focused on vocabulary mastery, grammatical structures, and text comprehension. These findings indicate that the textbook not only emphasizes the acquisition of fundamental Arabic language competencies but also integrates higher-order thinking skills through a balanced distribution of cognitive demands. The novelty of this study lies in its comprehensive mapping of LOTS, MOTS, and HOTS proportions in both learning exercises and end-of-semester evaluation questions of the Ayo Fasih Berbahasa Arab textbook for Grade XI based on the Revised Bloom’s Taxonomy, providing empirical evidence of the cognitive orientation of Arabic language textbooks used in Madrasah Aliyah.